Genetic and cellular studies highlight that A Disintegrin and Metalloproteinase 19 is a protective biomarker in human prostate cancer. Issue 1 (December 2016) - Hoyne, Gerard; Rudnicka, Caroline; Sang, Qing-Xiang; Roycik, Mark; Howarth, Sarah; Leedman, Peter; Schlaich, Markus; Candy, Patrick; Matthews, Vance
Abstract Background Prostate cancer is the second most frequently diagnosed cancer in men worldwide. Current treatments include surgery, androgen ablation and radiation. Introduction of more targeted therapies in prostate cancer, based on a detailed knowledge of the signalling pathways, aims to reduce side effects, leading to better clinical outcomes for the patient. ADAM19 (A Disintegrin And Metalloproteinase 19) is a transmembrane and soluble protein which can regulate cell phenotype through cell adhesion and proteolysis. ADAM19 has been positively associated with numerous diseases, but has not been shown to be a tumor suppressor in the pathogenesis of any human cancers. Our group sought to investigate the role of ADAM19 in human prostate cancer. Methods ADAM19 mRNA and protein levels were assessed in well characterised human prostate cancer cohorts. ADAM19 expression was assessed in normal prostate epithelial cells (RWPE-1) and prostate cancer cells (LNCaP, PC3) using western blotting and immunocytochemistry. Proliferation assays were conducted in LNCaP cells in which ADAM19 was over-expressed. In vitro scratch assays were performed in PC3 cells over-expressing ADAM19. Results Immunohistochemical studies highlighted that ADAM19 protein levels were elevated in normal prostate tissue compared to prostate cancer biopsies. Results from the clinical cohorts demonstrated that high levels of ADAM19 in microarrays are positively associated with lower stage (p = 0.02591) and reduced relapse (p = 0.00277) of human prostate cancer. In vitro, ADAM19 expression was higher in RWPE-1 cells compared to LNCaP cells. In addition, human ADAM19 over-expression reduced LNCaP cell proliferation and PC3 cell migration. Conclusions Taken together, our immunohistochemical and microarray results and cellular studies have shown for the first time that ADAM19 is a protective factor for human prostate cancer. Further, this study suggests that upregulation of ADAM19 expression could be of therapeutic potential in human prostate cancer.